The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/add.13721
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent drinking—a touch of social class?

Abstract: Adolescent drinking in Norway appears to be related inversely to parents' social standing. The elevated risk of low socio-economic status vanishes when general parenting, alcohol-related parental permissiveness and parents' drinking are accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 63 publications
4
28
1
1
Order By: Relevance
“…This is in line with a review of the literature that concluded that there is no clear pattern of association between alcohol use and socioeconomic status in adolescence [28]. Some studies have reported an inverse relationship between parents' socioeconomic status and adolescent drinking, but this relationship can probably be explained by differences between low and high socio-economic families in terms of the parent-child relationship, alcohol-related permissiveness and drinking with children present [29]. In the current study, we found that belonging one of the three groups with elevated drinking was predicted by frequency of seeing parents drunk.…”
Section: Trajectories Of Episodic Heavy Drinkingsupporting
confidence: 87%
“…This is in line with a review of the literature that concluded that there is no clear pattern of association between alcohol use and socioeconomic status in adolescence [28]. Some studies have reported an inverse relationship between parents' socioeconomic status and adolescent drinking, but this relationship can probably be explained by differences between low and high socio-economic families in terms of the parent-child relationship, alcohol-related permissiveness and drinking with children present [29]. In the current study, we found that belonging one of the three groups with elevated drinking was predicted by frequency of seeing parents drunk.…”
Section: Trajectories Of Episodic Heavy Drinkingsupporting
confidence: 87%
“…Parents' educational level was our main indicator for socioeconomic background. Previous analyses of the data set showed that a relatively small group with low-educated parents differed markedly from those with medium-or high-educated parents with respect to drinking (Norström et al, 2017;Pape et al, 2017). Whether the parents' educational level was high or medium barely made a difference, implying that the main social divide was between the lowest parental education group and all the others.…”
Section: Methodsmentioning
confidence: 93%
“…Such a differential impact of socioeconomic background also emerged in analyses of the frequency of alcohol use (Janssen, Pape (Jan 2018) 4 2016). Moreover, a Norwegian study showed that low parental SES was related more strongly to alcohol use by early teen youth as compared with mid-teen youth, whereas socioeconomic background did not make any difference among older teenagers (Pape et al, 2017). Thus, the more age-inappropriate the drinking, the stronger was the statistical impact of low parental SES.…”
mentioning
confidence: 99%
“…Moreover, Pape et al . —who analysed data from the same survey on which the present study is based—found that low SES was associated with early, frequent and heavy episodic drinking. Thus, the research literature offers some indirect indications that SES differences in youth violence in part may be due to differential exposure to the potential aggression‐arousing effects of alcohol.…”
Section: Introductionmentioning
confidence: 78%